1988
DOI: 10.1023/a:1015964907110
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A redox-based chemical delivery system for estradiol (E2-CDS) has been shown capable of sustained and brain-selective delivery of estradiol (E2). A reversed-phase high-performance liquid chromatographic (HPLC) method is presented for the analysis of E2-CDS and its oxidized quaternary metabolite (E2-Quat) in biological fluids or tissues. The assay utilized a precolumn enrichment technique and detects plasma levels down to 10 ng/ml E2-Quat and 20 ng/ml E2-CDS. Sample preparation is rapid and simple. Samples are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…In vitro experiments and distribution studies in rats showed a facile oxidation of 27 to 28 having a considerably longer t 1/2 in brain than that of those measured in peripheral tissues. 122,123 Pharmacokinetic studies in dogs revealed that 28 is rapidly eliminated from the periphery by both biliary and renal excretion, 124 but pharmacologically signi®cant amounts of it together with estradiol itself were measured in the CNS. 125 Pharmacological evaluation of the CDS in rats also con®rmed effects consistent with a long-lasting central estrogenization including decreased food intake, decreased body weight gain, libido enhancement, altered secretion of growth hormone and LH, and suppression of androgens and androgen-dependent tissues.…”
Section: B Steroidsmentioning
confidence: 99%
“…In vitro experiments and distribution studies in rats showed a facile oxidation of 27 to 28 having a considerably longer t 1/2 in brain than that of those measured in peripheral tissues. 122,123 Pharmacokinetic studies in dogs revealed that 28 is rapidly eliminated from the periphery by both biliary and renal excretion, 124 but pharmacologically signi®cant amounts of it together with estradiol itself were measured in the CNS. 125 Pharmacological evaluation of the CDS in rats also con®rmed effects consistent with a long-lasting central estrogenization including decreased food intake, decreased body weight gain, libido enhancement, altered secretion of growth hormone and LH, and suppression of androgens and androgen-dependent tissues.…”
Section: B Steroidsmentioning
confidence: 99%
“…The main human estrogen, 17β-estradiol (E2, Figure 1), has been undoubtedly the most studied compound to which the CDS approach has been applied [1,9,10,11,13,14], and is a typical example in this context. Although E2’s vast central effects [15,16] have allowed for the use of various in vivo experimental models for exploratory studies to observe attractive neuropharmacological responses, biopharmaceutical analyses focused specifically on E2 are still a formidable obstacle for the group pursuing the development of E2-CDS [9–11].…”
Section: Introductionmentioning
confidence: 99%
“…The solution was filtered, adjusted to 22% with respect to CH,CN, and subjected to HPLC with 22% CH,CN as the developing solvent. The periodate oxidation of meAMA in water has been found to yield two chemically similar forms of aldomeAMA which are apparently not free aldehydes and which interconvert in solution (6,9). The equilibrium mixture of these two forms will be referred to as aldomeAMA-IA/IB.…”
Section: Reagents and Chemicalsmentioning
confidence: 99%
“…The total yield in this case was 18.8 pmol (92%). Yet another form of aldomeAMA which has properties of a free aldehyde can be isolated from periodate oxidation reactions performed in acidic solutions (6,9). This material will be designated aldomeAMA-11.…”
Section: Reagents and Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation